Improvement of indoor location sensing algorithm using Wireless Local Area Network (WLAN) IEEE 802.11b - Yuen C.W.; Balasubramaniam N.; Din N.Md. (2023)
This paper proposes to improve the performance of the K-Nearest Neighbour algorithm in predicting the location of a mobile user in an indoor environment. Emphasis is placed on RSS sample vector fluctuation stabilization, resulting in an overall 12% increase in the precision of predicting correct locations compared to previous efforts. 2009 IEEE.